Application of PP-ECC in beam–column joint connections of rigid-framed railway bridges to reduce transverse reinforcements. (1st March 2015) - Zhang, Rui; Matsumoto, Koji; Hirata, Takayoshi; Ishizeki, Yoshikazu; Niwa, Junichiro
Highlights: The shear reinforcing effect of stirrups in PP-ECC beams. The feasibility of reducing shear rebars was confirmed by beam tests. Surface retarder was used to treat the interface bond between concrete and PP-ECC. PP-ECC can be a replacement of transverse reinforcements in beam-column joints. PP-ECC in beam-column joints can improve the workability and reduce congestion of rebars. Abstract: In the rigid-famed railway bridges, due to extensive amount of transverse reinforcements in the joint connections, the over congestion at the connection brings the difficulties in fabricating and casting. With the objective of avoiding the congestion, Polypropylene Fiber Reinforced Engineered Cementitious Composite (PP-ECC), as one kind of Engineered Cementitious Composites, was implemented to reduce the extensive amount of transverse reinforcements in the beam–column joint connection of rigid-framed railway bridges. The basic mechanical properties of PP-ECC were confirmed by compression and uniaxial tensile tests. The effects of reducing stirrup ratio in PP-ECC beams were investigated by four-point beam tests, including two normal reinforced concrete (RC) beams and five PP-ECC beams with stirrup ratios ranging from zero to 0.42%. Having confirmed the shear reinforcing effect of PP-ECC, three one-sixth scale beam–column joint connections were constructed and tested by applying a cyclic load. A specimen was prepared following the structural design of existing railway bridges in Japan but without transverse reinforcements in the joint. Further, two more specimens were prepared with reduced stirrups and ties in the beam and column, respectively. The experimental results reveal that the PP-ECC is effective in replacing transverse reinforcements in the beam–column joints of railway rigid-framed bridges.